If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.40x + 0.70(100) = 0.60(100 + x) Multiply 0.70 * 100 0.40x + 70 = 0.60(100 + x) Reorder the terms: 70 + 0.40x = 0.60(100 + x) 70 + 0.40x = (100 * 0.60 + x * 0.60) 70 + 0.40x = (60 + 0.60x) Solving 70 + 0.40x = 60 + 0.60x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.60x' to each side of the equation. 70 + 0.40x + -0.60x = 60 + 0.60x + -0.60x Combine like terms: 0.40x + -0.60x = -0.2x 70 + -0.2x = 60 + 0.60x + -0.60x Combine like terms: 0.60x + -0.60x = 0.00 70 + -0.2x = 60 + 0.00 70 + -0.2x = 60 Add '-70' to each side of the equation. 70 + -70 + -0.2x = 60 + -70 Combine like terms: 70 + -70 = 0 0 + -0.2x = 60 + -70 -0.2x = 60 + -70 Combine like terms: 60 + -70 = -10 -0.2x = -10 Divide each side by '-0.2'. x = 50 Simplifying x = 50
| 5x+1/x=6 | | 0.3(m-24)=0.6 | | 6p-3=4p+1 | | 4(14-1)/3(6)-5+7 | | 20x-12=68 | | 39.6x+19.6-40.5x-29.7= | | n+4.6=.7 | | -1.3x=-6.5 | | 55/9/10 | | 4+2x=5x+1 | | f^2+4f+16=0 | | 2x+1-1-x-(-x)-1=x-2x+1-(-x)-1 | | 5(1-(2w))+8w=15 | | 4x-3=x(2x-1) | | 7/4(s+3)=1/4-s | | -21m-42m=-2 | | -(5x-2y+7)= | | 13x+42=84 | | 4(-3x+1)=-10(x-4) | | 5/7+c=6 | | 4x+2x-1-1=2x | | 6((x+1)/2^3)+((-2x+3)/2^4)-3((3/2^2)x-1/2^2)+(3/2^3)*(3x-2)=0 | | 14-0.05(2x)=7-0.05(x) | | 9-6x=x | | 1=7-4x | | 0.75h+12.25=H | | 50x+15(60)= | | 7-14/5 | | y=9-3(-1)/5 | | 7/4(s+3)1/4-s | | (1/4)-(1/6) | | 12+7q=13+6q |